Desain Pelabuhan Wisata Untuk Menunjang Pariwisata Danau Toba - Amelia Azwar; Arif Fadillah; Shanty Manullang (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2020)
Tourist attractions in Indonesia have become a popular destination for domestic and foreign tourists. Lake Toba is a priority tourist destination, so this tourism has the potential to be developed as an asset that is used as a source of income for the nation and state. This research was conducted to plan the design of a tourist port and port management in the Lake Toba area with the availability of transportation ferries, tourist boats, water buses. The researched port planning uses very supportive facility standards referring to the port Master Plan Technical Guidelines, and PERMENPAR number 3 of 2018 by adding several facilities for the seaplane. bases and WIG ( Wing in Ground Effect ) are like runways amphibious that refer to U.S Department Of Transportation, Federal Aviation  Administration in the document Advisory Circular (AC) No. 150 / 5395-1B. For complete facilities at the port and seaplane bases, the method is used benchmarking by referring to the port ferry and seaplane. bases are the executive dock Merak Harbor, Singapore cruise center, Harbor Bay Batam, Jantzen Beach Seaplane Bases, Traves Seaplane Bases, Lake Hood Seaplane Bases. This port is planned to go through several stages of development using tourist visitor data with projected visits in the next 20 years. Based on the projection results, the highest number of passengers will occur in 2040 with 264,202 people.